The Illicit Commodification of Deportation: The Trump Administration’s “Third-Country Prisoner Transfer” Policy as a Violation of Jus Cogens Norms and the Law of State Responsibility - Nabiebu, Miebaka; Eja, Alobo Eni; Ipuole, Roland; Njong, Cleverty Afu (Pinisi Journal of Social Science, 2025)
This paper examines the Trump administration’s initiative to deport non-citizen prisoners to third countries through bilateral agreements as a fundamental challenge to international legal order. We argue this policy of “strategic exile” constituted an internationally wrongful act that engaged United States state responsibility by violating peremptory norms (jus cogens) and established principles of international law. The analysis demonstrates how the policy violated the prohibition on arbitrary deprivation of nationality and the right to a nationality, breached the absolute principle of non-refoulement, and contravened customary rules governing lawful expulsion. By seeking to transfer individuals to states with which they lacked genuine legal bonds, the United States attempted to create conditions of de facto statelessness while exposing individuals to foreseeable risks of persecution and indefinite detention. The paper further examines how recipient states could bear shared responsibility under the International Law Commission’s Articles on State Responsibility for aiding in these violations. This case represents a dangerous precedent for the erosion of fundamental human rights protections through bilateral coercion, demanding a robust international response to affirm that state sovereignty cannot legitimate the unilateral severance of an individual’s legal bond to the international community of states.